SUPPLIER SELECTION OPTIMIZATION FOR A CLOSED-LOOP SUPPLY CHAIN NETWORK: A COMPARATIVE ANALYSIS OF MCDM METHODS (Journal of the Management Sciences, 2025)
This study evaluates supplier selection optimization for a closed-loop supply chain network by comparing three multi-criteria decision-making methods which includes Weighted Sum, Weighted Product, and TOPSIS. The analysis focuses on raw material suppliers for sugar and PET bottles, assessing performance across eight key criteria, including cost, sustainability, lead time, and reliability. Findings reveal that 15% of suppliers achieve consistent top-tier performance (average score = 1.0), excelling in both operational and sustainability metrics (sustainability scores of 7.34-9.36 and on-time delivery rates of 0.91-0.97). Methodological disparities emerge, with Weighted Product being the most stringent (12-15% lower scores for mid-tier suppliers) and TOPSIS emphasizing balanced performance. Notably, suppliers with strong sustainability practices (average score = 8.2) outperform cost-focused counterparts by 92%, reinforcing circular economy principles. The study identifies critical performance thresholds, showing that suppliers scoring below 0.5 exhibit fundamental deficiencies (sustainability scores ≤ 3.2). These insights enable stratified supplier selection, highlighting elite performers for strategic partnerships and mid-tier suppliers for targeted development. The results provide a data-driven framework for optimizing closed-loop supply chains, aligning procurement strategies with sustainability and operational resilience.
Keywords: Supplier Selection; Closed-Loop Supply Chain; Topsis; Weighted Sum; Weighted Product, Sustainability